2021
DOI: 10.1002/mc.23279
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib inhibits migration, invasion, and vasculogenic mimicry of hepatocellular carcinoma via targeting ID1‐mediated EMT

Abstract: Regorafenib is approved for patients with unresectable hepatocellular carcinoma (HCC) following sorafenib. However, the effect of regorafenib on HCC metastasis and its mechanism are poorly understood. Here, our data showed that regorafenib significantly restrained the migration, invasion and vasculogenic mimicry (VM) of HCC cells, and downregulated the expression of epithelial-to-mesenchymal transition (EMT)/VM-related molecules. Using RNAseq and cellular thermal shift assays, we found that inhibitor of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The multi-targeted tyrosine kinase inhibitors like sorafenib and regorafenib have an established place in the systemic treatment for advanced HCC. It was reported that sorafenib (39) and regorafenib (40) could suppress the EMT of HCC cells. The expression levels of various molecules also change during EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-targeted tyrosine kinase inhibitors like sorafenib and regorafenib have an established place in the systemic treatment for advanced HCC. It was reported that sorafenib (39) and regorafenib (40) could suppress the EMT of HCC cells. The expression levels of various molecules also change during EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Since DCA is an important risk factor for promoting VM formation in intestinal tumors, it is necessary to investigate the specific molecular mechanism of this strong stimulation effect. The mechanisms promoting VM formation are very complex, among which EMT is the most studied 21,50 . EMT is a dynamic dedifferentiation process, where epithelial cells lose their typical epithelial features, such as apical‐basal polarity and cell adhesion, and acquire mesenchymal cell traits, such as motility and invasion, by downregulating epithelial genes and upregulating mesenchymal genes 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms promoting VM formation are very complex, among which EMT is the most studied. 21 , 50 EMT is a dynamic dedifferentiation process, where epithelial cells lose their typical epithelial features, such as apical‐basal polarity and cell adhesion, and acquire mesenchymal cell traits, such as motility and invasion, by downregulating epithelial genes and upregulating mesenchymal genes. 51 , 52 EMT, which is involved in biological processes such as embryonic development, organ formation, and tissue regeneration in adults, has received more attention in the past two decades due to its potential role in the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations